Synthesis, acetylcholinesterase and molecular modelling analysis of (3E,5E)-3,5-Diarylidene-1-Phenylethylpiperidine-4-one derivatives as a therapeutic agent for Alzheimer’s disease - Mohd Khairul Nizam Mazlan,; Mohamad Nurul Azmi,; Mohd Salleh Rofiee,; Muntaz Abu Bakar,; Muhammad Solehin Abd Ghani,; Mohammed Tasyriq Che Omar,; Thaigarajan Parumasivam,; Mohd Fazli Mohammat,; Wibowo, Agustono (Penerbit Universiti Kebangsaan Malaysia, 2025)
New diarylidiene-1-phenylethylpiperidine-4-one derivatives 2a-h were successfully synthesised with yields ranging from 57% to 96% and characterised with various spectroscopic methods. The compounds were evaluated for their in vitro acetylcholinesterase inhibition activity with galantamine as positive control. Among the synthesised compounds, compounds 2g and 2h were found to be most potent against acetylcholinesterase enzyme with half-maximal inhibitory concentration (IC50)of 46.3 ± 0.53 µM and IC50 = 29.7 ± 0.41 µM, respectively. The binding energy and interaction of compounds 2g and 2h with acetylcholinesterase protein were further studied through molecular docking studies. Compound 2h (-12.1 ± 0.0 kcal mol -1 )showed a strong binding affinity than compound 2g (-10.6 ± 0.0 kcal mol -1 ) and both compounds exhibit several binding interactions with amino acids in acetylcholinesterase protein. The molecular docking studies of these compounds supports the in vitro acetylcholinesterase inhibition activity, suggesting that diarylidene phenylethyl-1-piperidone scaffold might be a promising drug candidate for a new acetylcholinesterase inhibitor drug development.